Analysis of the Level of Upper Service Skills in Volleyball Games of Junior High School Extracurricular Students - Muhammad Fadli (Jurnal Pendidikan Kepelatihan Olahraga: PEJUANG, 2026)
This study aimed to determine the level of overhand serve ability in volleyball among students of SMP Negeri 24 Makassar. A quantitative approach with a descriptive method was employed. The sample consisted of 20 students selected through total sampling, meaning the entire population served as research subjects. The research instrument was an overhand serve skill test conducted with the involvement of an observer, supported by observation and interviews as supplementary data. The results revealed that the overhand serve ability of students at SMP Negeri 24 Makassar falls under the good classification with a percentage of 35.0%. This study concludes that the overhand serve skills of students at SMP Negeri 24 Makassar are generally considered good; however, further improvement remains necessary given that the serve is a fundamental technique that every player must master, as it directly influences the opportunity to score points in a match. Therefore, integrated training encompassing basic techniques such as passing, blocking, smashing, serving, and physical conditioning needs to be consistently maintained to support more optimal overhand serve performance.